Orbital Metastasis Secondary to Merkel Cell Carcinoma: Case Report and Literature Review. (August 2013) - Johnson, Davin; Warder, Daniel; Plourde, Marc-Emile; Brundage, Michael; ten Hove, Martin
Abstract Introduction: Merkel cell carcinoma is an aggressive malignancy often associated with metastatic spread, but has never been reported to metastasize to the orbit. Case: An 80 year old male with metastatic Merkel cell carcinoma presented with ptosis and extraocular movement abnormalities, and was found to have a lesion of the orbit consistent with metastatic spread. The lesion responded favorably to radiation therapy. Comment: Although the orbit is a frequent site of metastatic disease, this is the first reported case of presumed Merkel cell carcinoma metastasizing to the orbit.